2021
DOI: 10.1155/2021/9990219
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Assessment of Pesticide Ingestion with Fruit and Vegetables for Consumer’s Health

Abstract: Pesticides are chemicals used in agriculture to protect crops from pests. In addition to protection during cultivation, they are also used after harvesting to extend the shelf life of products. Postharvest control stands out, especially when it comes to products imported from distant countries, resulting in increased concentration of pesticides and risk to human health consuming such products. In this study, analyses of pesticide residues were performed on 200 samples of fruits and vegetables. Pesticide residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Therefore, our QAC waxes may be formulated into wax blends or existing emulsions to curtail the pervasive use of imazalil, for example, as there exist environmental and biological concerns with its use due to bioaccumulation. 25 Antimicrobial Activity of QAC Waxes. Antibacterial Activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our QAC waxes may be formulated into wax blends or existing emulsions to curtail the pervasive use of imazalil, for example, as there exist environmental and biological concerns with its use due to bioaccumulation. 25 Antimicrobial Activity of QAC Waxes. Antibacterial Activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We formulated our QAC waxes into carnauba wax and beeswax blends at up to 50 wt % and observed only a minor 1–5 °C decrease in the melting point of these materials and no significant phase separation as judged by the enthalpy of melting (Supporting Figure 2). Therefore, our QAC waxes may be formulated into wax blends or existing emulsions to curtail the pervasive use of imazalil, for example, as there exist environmental and biological concerns with its use due to bioaccumulation …”
Section: Resultsmentioning
confidence: 99%
“…In a study by Jurak et al [77], pesticide residues were detected in 31 out of 200 (15.5%) samples of fruits (oranges, grapefruits, lemons, mandarins, peaches, pears, grapes) and vegetables (tomato, potato). In fruit samples, pesticide residues were found in 22 out of 120 (18.3%) analysed samples.…”
Section: Citrus Fruitsmentioning
confidence: 97%
“…In a study on apples and lemons, Jurak et al [77] demonstrated that 18.3% of analysed samples were contaminated with pesticides. The most frequently identified compound was izmalil, detected in 18 analysed samples (range of 0.02-4.10 mg/kg), followed by chlorpyrifos, identified in 8 samples, at concentrations from 0.03 mg/kg to 0.27 mg/kg.…”
Section: Citrus Fruitsmentioning
confidence: 99%
“…Um estudo recente sobre o risco de consumir frutas e legumes com resíduos de agrotóxicos na Croácia, concluiu que, em experimentos com animais, o fungicida imazalil exerceu alto potencial inflamatório e causou leucocitose(JURAK et al, 2021). Os resultados indicaram bioacumulação do agrotóxico em órgãos do corpo, mesmo com o uso de baixas doses por um longo período.…”
unclassified